Imagens, mitemas e mitos em “A princesa e a costureira” e “Joana princesa”: construções discursivas de identidades sexuais - Silva, Clodoaldo Ferreira Fernandes da (2018)
This study presents a research which was conducted under the auspices of the PhD Program in Letters and Linguistics at the Federal University of Goiás (UFG) between the years of 2015 and 2018. The investigation – Images, mythemes and myths in “The princess and the seamstress” and Princess Joana: discursive constructions of sexual identities, research follows a qualitative approach and investigates how sexual dissidences reconfigure gender identities in children's stories. The central objectives are to examine the myths in the narratives of contemporary fairy tales and to verify if they can (de)construct some identities. It is also intended to problematize myths which can possibly produce identities, as well as to investigate how the ideas expressed in the stories can insert or exclude sexual diversity in the contemporary world. Another purpose of the research is to discuss the relationship between gender identities constructed in the stories and their socially pre-established roles, in order to analyze how the myth is proposed in contemporary narrative of fairy tales. The corpus of our analysis was made up of two fairy tales written by Janaína Leslão which were published in Brazil from 2015 to 2016. These tales were entitled The Princess and the Seamstress, and Princess Joana. The analysis of the texts followed the theoretical and methodological principles of the Anthropology of the Imaginary and the interpretations were subsidized by the scientific method named mythcritic as proposed by Gilbert Durand. The results indicate that there is a renewal of the myths that subsidize new identity constructions about sexual dissidences.